The Implementation of Regional Regulation Number 2 of 2024 Concerning Regional Taxes and Regional Levies on the Original Regional Revenue of Southeast Sulawesi Province - Alfa Sari Ode Rusli; Muh. Nur; Mahmudin A. Sabilalo (Jurnal Indonesia Sosial Teknologi, 2025)
The implementation of regional tax and retribution collection policies is crucial for increasing regional revenue independence and reducing dependence on central government transfer funds. This study aims to analyze the implementation of Southeast Sulawesi Provincial Regulation Number 2 of 2024 Concerning Regional Taxes and Regional Retributions, identify constraints faced, and examine efforts made to overcome these constraints. This research employed a descriptive qualitative method conducted at the Regional Revenue Agency of Southeast Sulawesi Province from January to March 2025. Data were collected through in-depth interviews with key informants, observation, and documentation study. Data analysis used the interactive model of Miles and Huberman. The results show that: (1) policy implementation based on George C. Edward III's model has been running well in terms of communication, resources, disposition, and bureaucratic structure; (2) constraints include low taxpayer awareness and limited human resource quality and quantity; (3) efforts made include massive socialization and education programs, and capacity building through technical training. The study concludes that, while implementation has been effective, continuous efforts are needed to enhance taxpayer compliance and improve human resource capacity for optimal regional revenue collection.